2011
DOI: 10.1257/aer.101.5.2205
|View full text |Cite
|
Sign up to set email alerts
|

The Area and Population of Cities: New Insights from a Different Perspective on Cities

Abstract: The distribution of city populations has attracted much attention, in part because it constrains models of local growth. However, there is no consensus on the distribution below the very upper tail, because available data need to rely on "legal" rather than "economic" definitions for medium and small cities. To remedy this difficulty, we construct cities "from the bottom up" by clustering populated areas obtained from high-resolution data. We find that Zipf's law for population holds for cities as small as 5,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
262
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(275 citation statements)
references
References 48 publications
12
262
0
1
Order By: Relevance
“…Similar conceptualizations dominated the scientific discourse during the twentieth century, epitomized by Zipf's and Gibrat's laws. While the application of these laws to city size and urban growth still remains an open problem [7,8], during the last decades fractal theory and diffusion processes found fertile applications to morphological studies of urban systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similar conceptualizations dominated the scientific discourse during the twentieth century, epitomized by Zipf's and Gibrat's laws. While the application of these laws to city size and urban growth still remains an open problem [7,8], during the last decades fractal theory and diffusion processes found fertile applications to morphological studies of urban systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Rozenfeld et al found the similar result too in the process of studying the area and population of cities. They found the power-law distribution of areas with an exponent close to 1 [20]. Although the area of Ref.…”
Section: Introductionmentioning
confidence: 94%
“…Although the area of Ref. [20] is not the same as the cell enclosed by the streets, it is also meaningful for us to know the universal law of the area distribution.…”
Section: Introductionmentioning
confidence: 99%
“…City areas have been decided by geographical, historical, and administrative factors. Rozenfeld et al proposed a method that decided a city's area by a city clustering algorithm [10]. In this research, we divide spatial regions by a method that ignores the shape of cities to find the properties of population distribution that do not depend on countries or local regions.…”
Section: Introductionmentioning
confidence: 99%